Study of Optimization Darrieus Wind Turbine Using Numerical Investigation - Susanto, Edy; Paryanto, Paryanto; Hadiyanto, Hadiyanto; Permata, Ariyo Nurachman Satiya; Setiawan, M. Yasep (Universitas Sultan Ageng Tirtayasa, 2024)
Utilization of electric resources keep on expanding due to social and mechanical progression. Different sorts of sources are utilized to fulfill the resources needs. Wind resources is additionally a source which fulfills a portion of electric energy needs with the assistance of wind turbine. the Darrieus Wind Turbine on the performance of the Vertical Shaft Wind Turbine (VAWT) is utilized for its extraordinary potential in application to its auxiliary advantage and omni-directionality. Three diverse wind speeds were considered within the examination with the NACA 4415 airfoil sort. The wind speeds were shifted based on wind speeds at 15 m/s, 20 m/s and 25 m/s. From the numerical examination, it was found that the optimal result was gained by 4 blade variations due to less turbulence that appeared.